Gender Representations in Fitness Advertisements from the #Yoentrenoencasa Community - López López, Claudia; López-Villar, Cristina (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Over the years, the fitness industry has increased its activity on social media and Instagram has become a marketing tool. This study aims to analyze gender representations in content shared by fitness centers on Instagram under the hashtag #Yoentrenoencasa. A thematic analysis of the visual content and linguistic messages of the fitness ads of this community was carried out, revealing the reproduction of gender stereotypes linked to sport and the perpetuation of sexist roles, putting women in decorative visions compared to the professional roles of men.